Teknologi dalam Rantai Pasok Agribisnis: Analisis Bibliometrik tentang Perannya dalam Meningkatkan Ketahanan Pangan - Annisa Vira Widayanti; Raka Selaksa Charisma Muchammad; Akbar Hariputra; Aditya Arief Rachmadhan (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2025)
Climate change, global disruptions, and unequal food distribution have made food security a critical and urgent global issue. In response, digital technologies offer strategic opportunities to enhance the efficiency, transparency, and resilience of agribusiness supply chains. However, existing research remains fragmented, often lacking thematic integration and a global perspective on how digital innovations contribute to food security. This study aims to systematically map the global research landscape through a bibliometric analysis of 100 Scopus-indexed articles published between 2019 and 2025, focusing on the intersection of digital technology, agribusiness, and food security. Using VOSviewer, five major thematic clusters are identified: blockchain and traceability, digital supply chain platforms, artificial intelligence, sustainability transformation, and data-driven agribusiness. The findings show that technologies such as blockchain, IoT, and AI play a vital role in supporting food system availability, accessibility, and stability. Emerging topics such as circular economy and digital inclusion reflect a shift toward more sustainable and equitable digital food systems. This study not only synthesizes existing academic discourse but also provides strategic insights for future research, policy design, and inclusive technological adoption—particularly in developing regions. As such, it serves as an essential foundation for designing systemic, inclusive, and sustainable digital transformation in agrifood systems to address the urgent challenge of global food security.